Evaluating the repeatability of RTK GPS measurements using analysis of variance - Pirti, Atinç (Geodetski vestnik, 2012)
The purpose of this study is to evaluate the repeatability of RTK GPS method under varying satellite configurations by using different reference points. Furthermore, we conducted one way Analysis of Variance (ANOVA), which is a powerful tool for comparing the variability of related types of measurements. Multi-reference station is a well-known approach in RTK GPS. Using multi-reference points is an effective way to achieve consistent accuracy in the whole net by making errors less distance dependent on the reference stations. It is possible to achieve high reliability and availability by usingmulti-reference stations. If one station goes down or starts to provide suspicious values, it is possible to compensate the situation with other stations, while this is not possible when a single reference station fails. Here we present ANOVA which is an effective method to check the quality of corrections generated from each reference station.
Keywords: accuracy; ANOVA; geodesy; geodezija; GPS; meritve; natančnost; ponovljivost; repeatability; RTK GPS